Design and evaluation of sustained-release vildagliptin tablets using natural plant mucilages as functional polymers - Poonam Taru; T. S. Shanmugarajan; E. Bhavya (Journal of Applied Pharmaceutical Research, 2026)
Background: Natural plant-derived mucilages are gaining attention as biodegradable and biocompatible alternatives to synthetic polymers in sustained-release drug delivery systems. This study focuses on the development of prolonged-release matrix tablets of Vildagliptin using mucilages from Mimosa pudica seeds and Tinospora sinensis stems for improved glycemic control in type II diabetes mellitus. Methodology: Mucilages were extracted by aqueous extraction and evaluated for physicochemical properties. The swelling index ranged from 250–280%, with a near-neutral pH (6.5–7.0). Matrix tablets were prepared by direct compression and assessed for hardness (5.2–6.1 kg/cm²), friability (<1%), weight variation, and drug content (98.2–101.4%). In vitro drug release studies were conducted for 12 hours. Drug–polymer compatibility was analyzed using FTIR spectroscopy, and release kinetics were evaluated using mathematical models. Results and Discussion: FTIR analysis confirmed the absence of drug–polymer interactions. The optimized formulation showed 96.8% cumulative drug release over 12 hours, indicating effective sustained-release performance. The release followed the Korsmeyer–Peppas model (R² = 0.97) with anomalous (non-Fickian) transport, suggesting a combination of diffusion and polymer erosion mechanisms. The combination of the two mucilages demonstrated superior release control compared to either polymer alone. Conclusion: Mimosa pudica and Tinospora sinensis mucilages exhibit strong potential as natural matrix-forming agents for sustained-release formulations of Vildagliptin, providing a sustainable, cost-effective alternative to synthetic polymers.